GOVERNMENT VIRTUAL PRIVATE DATA CENTER BASED ON CLOUD COMPUTING (EMPIRICAL STUDY ON INDONESIAN INSTITUTE OF SCIENCES - LIPI) - Wahyu Setyo Prabowo; Muhammad Hanif Muslim; Syam Budi Iryanto (Jurnal Penelitian dan Pengembangan Komunikasi dan Informatika, 2015)
Advantages of Cloud Computing (CC) is a new technology that has the characteristics of on-demand self-service, broad network access, resource pooling, rapid elasticity, and measured service, which promises efficiency and operational effectiveness of Information and Communication Technology (ICT) in the organization. CC Problems in supporting the performance of Government Institutions still have not been of particular concern. This article presents the results of CC-based data center migration (Virtual Private Data Center) is applied to the Indonesian Institute of Sciences (LIPI). The application of the model is expected to be a reference to other government agencies that have the characteristics and allied with LIPI and other government agencies in implementing ICT management to get more benefit from the CC so that the effectiveness and efficiency of ICT management can be achieved.Keywords: cloud computing; virtual private data center; government agencies; LIPI